Epistemic network analysis of online learning engagement models a quantitative ethnography - Barcelona, Alvin B. (College of Education, University of the Philippines Diliman, 2022)
Traditional ethnography has predominantly been associated with a qualitative methodological orientation. However, ethnographers are challenged to process and analyze cultural systems with voluminous data. This predicament catalyzed the need for an emerging methodology to assess learning and complex thinking in digital environments by using statistical tools to analyze qualitative data. Quantitative Ethnography (QE) blends qualitative and quantitative approaches and uses statistical tools in analyzing qualitative data. This study advanced Epistemic Network Analysis (ENA), a QE tool to analyze the online learning engagement of teachers and students. Observation of synchronous classes and asynchronous activities were carried out, utterances were coded, and network models of engagements were generated. The findings show that the ENA engagement model among teachers and students in synchronous and asynchronous sessions were significantly different, with the teachers giving more frequent and varied feedback during synchronous classes. Also, the structure of engagement differs according to the academic strands of the students. The network models of engagement in synchronous classes reveal the co-occurrence of students' cognitive engagement and teachers' feedback: connecting-corrective and informative content feedback, extending-affective and informative content feedback while prompt-connecting and emancipating and simply-agreeing-affective and informative procedural feedback were found to be prevalent during asynchronous classes. Moreover, the multiple regression analysis and interview data show that self-regulated behavior among students, teacher's presence, and parental involvement are significant predictors of cognitive engagement among students. This study illuminates the methodological advantages of ENA as an ethnographic tool that mixed qualitative and quantitative approaches in understanding cultural systems and processes in education.